Cybernetic Theory in Improving Students' Higher Order Thinking Skill - Nasution; Safirah, Adita Dwi; Wiryanto; Muhimmah, Hitta Alfi; Abdillah, Moh. Irfan (MIMBAR PGSD Undiksha, 2024)
The rapid development of knowledge and technology in the 21st century era, education is very important in facing global challenges. Students are required to have higher order thinking skills. Education plays an important role in shaping students' HOTS in facing challenges in the current era. The purpose of this study was to analyze the effect of implementing cybernetic theory on HOTS. This type of research is a quasi-experimental design with a non-equivalent control group design. The population of this study were fourth grade elementary school students, totalling 42 students. The sample of this research was class IV A with 20 students and class IV B with 22 students. Class IV A is an experimental class that does learning with cybernetic theory, while class IV B is a control class that does conventional learning. Methods in data collection are interviews and tests. The instruments used in data collection were interview sheets and multiple-choice tests. Data were analyzed with quantitative descriptive and independent sampling t test. The results of the t-test that have been carried out obtained a t-count value of 9.645 with a t-table of 1.684. This means that t-count > t-table so that Ha is accepted and Ho is rejected. So, it can be concluded that there is a significant effect of the application of cybernetic theory on the HOTS of fourth grade elementary school students. Therefore, the use of cybernetic theory can be an effective approach in developing HOTS at the elementary school.